Interceptive Orthodontics : a Practical Guide to Occlusal Management. - Noar, Joseph (Wiley, 2014)
Identify problems and introduce solutions early for an ideal aesthetic result Interceptive Orthodontic saims to guide the practitioner in the art of interceptive management of the developing dentition. The goal is to guide the permanent dentition into the line of the dental arches, avoiding complex orthodontic treatment for teeth displaced far from their ideal position, and thereby reducing orthodontic treatment time. This book covers growth of the jaws and tooth development, and explains the correct timing of interceptive management. It also discusses orthodontic asse.